2019
DOI: 10.32098/mltj.01.2016.04
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive capsulitis of the shoulder and diabetes: a meta-analysis of prevalence

Abstract: Background: adhesive capsulitis (AC) results in progressive painful restriction in range of movement and can reduce function and quality of life. Whilst it has been associated with diabetes mellitus (DM), there is considerable variation in the reported prevalence of AC in the diabetic population. The aim of this study is to determine through meta-analysis the prevalence of AC in DM and examine whether it is influenced by type of DM or insulin therapy. We also aim to further establish the prevalence of DM in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(37 citation statements)
references
References 32 publications
2
32
0
3
Order By: Relevance
“…The percent of female subjects in each group was 58.3% and 62.5% for Group A and B, respectively, with an age range from 48 to 59 years and a mean BMI of 37.63 kg/m 2 . These patient characteristics are consistent with other studies, where AC was more common in obese women in the fifth decade of age [32,33] and can affect daily living activities with a reduction in the quality of life due to different degrees of shoulder ROM limitation [3].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The percent of female subjects in each group was 58.3% and 62.5% for Group A and B, respectively, with an age range from 48 to 59 years and a mean BMI of 37.63 kg/m 2 . These patient characteristics are consistent with other studies, where AC was more common in obese women in the fifth decade of age [32,33] and can affect daily living activities with a reduction in the quality of life due to different degrees of shoulder ROM limitation [3].…”
Section: Discussionsupporting
confidence: 91%
“…Many painful musculoskeletal conditions that interfere with regular daily activity, including trigger finger, carpal tunnel syndrome, osteoarthritis, and frozen shoulder, are associated with diabetes mellitus (DM) [1]. Adhesive capsulitis (AC) (also referred to as frozen shoulder) is characterized by severe shoulder pain [2] with advanced limitation of the joint range of motion associated with functional disability [3], that negatively affects life quality and care costs [4]. AC is caused by inflammation and results in tissue fibrosis, which might lead to joint capsule tightness [5].…”
Section: Introductionmentioning
confidence: 99%
“…Frozen shoulder (FS) or adhesive capsulitis is one of the most common orthopedic conditions affecting the shoulder, with prevalence of 2–5% in the general population [13]. This condition commonly occurs between 40 and 60 years of life, with the peak age in the mid-50s [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prevalence of diabetes among the patients with ACoS was determined to reach 30%. Therefore, the authors suggested screening for diabetes should be considered for patients with ACoS [14]. Rai et al reported rates of 15.5% and 27.4% for prediabetes and diabetes, respectively, among the patients with ACoS.…”
Section: Discussionmentioning
confidence: 99%